Thermal Behavior of an Asphalt Pavement in the Laboratory and in the Parking Lot - J. B. Martinkauppi; A. Mäkiranta; J. Kiijärvi; E. Hiltunen (The Scientific World Journal)
The urban, constructed areas are full of buildings and different kinds of pavements and have a noticeable lack of trees and flora. These areas are accumulating the heat from the Sun, people, vehicles, and constructions. One interesting heat collector is the asphalt pavement. How does the heat transfer to different layers under the pavement or does it? What are the temperatures under the pavement in Finland where the winter can be pretty hard? How can those temperatures be measured accurately? These are the main questions this paper gives the preliminary answers to. First the thermal behavior of asphalt and the layers beneath are researched in the laboratory and then the measurement field is bored and dug in the parking in the Western coast of Finland, 63°5′45′′ N. Distributed temperature sensing method was found to be a good choice for temperature measurements. Thermal behavior of pavement has been monitored in different layers and the preliminary results have been published here. The goal of this research is to assess the applicability of asphalt pavements for heat energy collection.